2006
DOI: 10.1128/aac.50.1.185-195.2006
|View full text |Cite
|
Sign up to set email alerts
|

Two Cathelicidin Genes Are Present in both Rainbow Trout ( Oncorhynchus mykiss ) and Atlantic Salmon ( Salmo salar )

Abstract: Further to the previous finding of the rainbow trout rtCATH_1 gene, this paper describes three more cathelicidin genes found in salmonids: two in Atlantic salmon, named asCATH_1 and asCATH_2, and one in rainbow trout, named rtCATH_2. All the three new salmonid cathelicidin genes share the common characteristics of mammalian cathelicidin genes, such as consisting of four exons and possessing a highly conserved preproregion and four invariant cysteines clustered in the C-terminal region of the cathelin-like doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
116
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 36 publications
9
116
0
7
Order By: Relevance
“…The cells were washed immediately with culture medium and incubated at 20 C for 6 h. The RNA preparation and real-time PCR analysis was as described above. The genes studied by real time PCR were trNOD2 (this paper), IRF3 and IRF7 [26], IFN1 and IFN2 [19], IFN-g1 [23], IFN-g2 [27], IL-1b1 [28], IL-6 [29], IL-8 [30], TNFa [31], CATH2 [32], caspase-1 (TC Number of rainbow trout EST, TC172333), -2 (TC Number of rainbow trout EST, TC170354), -3 (TC Number of rainbow trout EST, TC148559), -6 [24], -7 (TC Number of rainbow trout EST, TC154414), -8 (TC Number of rainbow trout EST, TC133215), and -9 (GeneBank accession no. NP_001118119).…”
Section: Modulation Of the Inflammasome And Apoptosis Signaling Pathwmentioning
confidence: 98%
See 1 more Smart Citation
“…The cells were washed immediately with culture medium and incubated at 20 C for 6 h. The RNA preparation and real-time PCR analysis was as described above. The genes studied by real time PCR were trNOD2 (this paper), IRF3 and IRF7 [26], IFN1 and IFN2 [19], IFN-g1 [23], IFN-g2 [27], IL-1b1 [28], IL-6 [29], IL-8 [30], TNFa [31], CATH2 [32], caspase-1 (TC Number of rainbow trout EST, TC172333), -2 (TC Number of rainbow trout EST, TC170354), -3 (TC Number of rainbow trout EST, TC148559), -6 [24], -7 (TC Number of rainbow trout EST, TC154414), -8 (TC Number of rainbow trout EST, TC133215), and -9 (GeneBank accession no. NP_001118119).…”
Section: Modulation Of the Inflammasome And Apoptosis Signaling Pathwmentioning
confidence: 98%
“…In rainbow trout, Chang et al [32] have previously identified two cathelicidin genes, with the expression of cathelicidin-2 (cath2) high in RTG-2 cells. Thus, we next examined the expression of cath2 in cells tranfected with the trout NOD2 effector ptGFP1-trNOD2a CARD, ptGFP1-trNOD2b CARD, ptGFP1-NACHT or ptGFP1-LRR plasmid.…”
Section: Modulation Of Inflammatory Cytokine and Amp Expression By Trmentioning
confidence: 99%
“…By screening cDNA libraries or by using molecular methodology, putative cathelicidins have been found from rainbow trout [159], Atlantic salmon [174], Arctic char (Salvelinus alpines), Atlantic cod, and brook trout (Salvelinus fontinalis) [175]. Moreover, cathelicidin genes have been reported for jawless fish, namely, the Atlantic hagfish (Myxine glutinosa) [176].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Moreover, cathelicidin genes have been reported for jawless fish, namely, the Atlantic hagfish (Myxine glutinosa) [176]. Little information is available with respect to the native peptides, but synthetic rainbow trout cathelicidins are active against Gram-positive and Gram-negative bacteria [174].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Although numerous previous studies predicted mature peptide only against valine, in current work we consult the sequences alignment result (Fig. 3), aided with enzymatic cleavage study carried out by Chang et al [12], where a full-length recombinant protein and Western blot analysis were explored followed by a precise mass spectroscopic confirmation. Thus, threonine (146) of prepropeptide is assumed to be the processing site for B. lenoks elastase-like protease to generate the mature peptide, CATH_BRALE.…”
Section: Cleavage Site Predictionmentioning
confidence: 99%